CERN to Gran Sasso; an ideal distance for superbeam? - Minakata, Hisakazu; Nunokawa, Hiroshi [UNESP] (Elsevier, 2002)
We use the CP trajectory diagram as a tool for pictorial representation of the genuine CP and the matter effects to explore the possibility of an in situ simultaneous measurement of δ and the sign of Δℳ13 2. We end up with a low-energy conventional superbeam experiment with a megaton-class water Cherenkov detector and baseline length of about 700 km. A picturesque description of the combined ambiguity which may arise in simultaneous determination of θ13 and the above two quantities is given in terms of CP trajectory diagram.